Syrian Arab Republic country report - Kaisi A.; Yasser M.; Mahrouseh Y. (Non-conventional water use: WASAMED project, 2005)
Growing population results in a great pressure on limited water resources (WRs) prone to depletion. As a result of the rising water demand by agriculture, industry and tourism, so it is necessary to cope with these circumstances by increasing water use rationalization. But this solution can't alone solve the problem for a long time, therefore we shouldn't use sewage water as a traditional source where treated wastewater reuse in agriculture became one of the most important solutions for providing irrigation water as a substitute for fresh water in irrigation. Accordingly, we should take several steps to avoid the adverse impacts of sewage water, select the appropriate irrigation methods, raise the awareness of farmers on health and environmental issues, and find standards for using this kind of water.
3. WASAMED (WAter SAving in MEDiterranean agriculture) Workshop, 2004/12/07-10, Cairo (Egypt)